The Correlation between Characteristics, Knowledge and Motivation of Couples in Childbearing Age with the Early Detection of Cervical Cancer in Ulin General Hospital Banjarmasin - Anggrita Sari; Ika Mardiatul Ulfa; Dewi Pusparani Sinambela (International Journal of Clinical Inventions and Medical Sciences, 2020)
Cervical cancer is a malignant tumor that grows in the cervix and often attack women. In Indonesia cervical cancer is the number one killer of all cancers. So early detection is very important. The incidence of cancer from year to year has been increasing significantly. On the contrary, the coverage of pap smear test has been decreasing. The aims are to determine the correlation of characteristics (age, education, and employment), knowledge and motivation and early detection of cervical cancer in couples of childbearing age in patients of Ulin General Hospital Banjarmasin. This type of research is analytic survey with cross sectional. The population is all couples of childbearing age who visit in obstetrics policlinic in Ulin General Hospital Banjarmasin. Sampling method was done by accidental sampling using a sample size of 30 people. Analysis using the spearman rank correlation test with 95% confidence value. Results find no correlation between age and early detection of cervical cancer (p=0,264>α=0,05), a correlation between education and early detection of cervical cancer (p=0,001<α=0,05), a correlation between employment with early detection of cervical cancer (p=0,003<α=0,05), no correlation between knowledge with the early detection of cervical cancer (p=0,425>α=0,05)), no correlation between motivation with the early detection of cervical cancer (p=0,264>α=0,05).